Analisis Penerapan PSAK 71 Dalam Penyajian Cadangan Kerugian Penurunan Nilai Dan Kinerja Keuangan Perusahaan Perbankan - Muhammad Ponco Wibowo; Siti Ita Rosita (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
In 2020 companies in Indonesia have to implement PSAK 71 to replace PSAK 55. With the forward looking Expected Credit Loss approach in PSAK 71, profit of the banking industry has the potential to be declining because banks have to prepare Allowance for Impairment Losses since the initial recognition of financial assets. This study aims to find out the application of PSAK 71 in the presentation of allowance for impairment losses on banking companies in Indonesia and examine its financial performance using the CAMEL method. This research was conducted at CTBC Bank of Indonesia The type of data used in this study is secondary data which was obtained in the form of annual reports containing audit reports and other additional information. The analysis of the data is intended to find out whether the presentation of allowance for impairment losses at CTBC Bank is in accordance with PSAK 71 or not, and analyze the company’s financial performance The results of this study show that CTBC Bank of Indonesia has implemented PSAK 71 of allowance for impairment losses properly and the recalculation of impairment losses was in accordance with transitional provisions of PSAK 71 in 2017. This reduced the value of Bank’s CAMEL by 3,33 resulting from the decrease of net income and total assets. However, as of December 31, 2018 the company has succeeded in raising the CAMEL value to 85,55 and achieved a rating of healthy status from Bank Indonesia Keywords:PSAK 71, Impairment losses, CAMEL, financial instrument